EVALUATION OF PHYTOCHEMICAL ANALYSIS AND ANTIOXIDANT AND ANTIFUNGAL ACTIVITY OF PITHECELLOBIUM DULCE LEAVES’ EXTRACT - Kumari, Suman (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Diseases due to pathogenic fungi represent a critical problem to human health which is a major cause of morbidity and mortality worldwide. Synthetic drugs such as Amphotericin B mitigate many of the side effects associated with liver and kidney dysfunctions. Widely distributed traditional medicinal plants-based antimicrobial drugs are cost effective in the treatment of infectious diseases having no side effects. Pithecellobium dulce (Roxb.) belongs to the family of Leguminosae, is an evergreen tree widely distributed in the greater part of India which has been widely used in traditional medicine, but lacks scientific scrutiny. The present study revealed P. dulce extract effectiveness against A. fumigates and Aspergillus niger and showed antioxidant activity. Methods: Leaves’ extract was prepared according to the polarity of solvent, i.e., hexane, chloroform, acetone, methanol, and water. Phytochemical analysis, antioxidant activity, and minimum inhibitory concentration (MIC) were tested against selected fungus. Results: Phytochemical analysis of the extract revealed the presence of alkaloids, flavonoids, saponins, coumarin, tannins, anthocyanin, and triterpenoids. Methanol and water extract was found to contain significant amounts of alkaloids, phenols, and flavonoids. Methanolic extract showed MIC against tested fungus, and extract was further fractionated by solvent-solvent fractionation and MIC was tested. MIC for A. fumigatus was0.62 mg/ml and for A. niger was 1.25 mg/ml, and the results were comparable with effective synthetic drug Amphotericin B. Conclusion: Extract possesses potent fungicidal activity which, in turn, may be due to the presence of biologically active ingredient. Keywords: Antioxidant activity, Phytochemical activity, Antifungal activity, Minimum inhibitory concentration, Fractionation